2022
DOI: 10.1039/d2ra05992d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic properties of two fluorescent fac-Re(CO)3 complexes bearing an N,N-bidentate benzimidazole coligand

Abstract: Tricarbonyl Re(i) complexes are piled in the intercellular junction and diffused inside the cells. This led to DNA fragmentations and both apoptotic and necrotic cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…33,36−43 However, their in vivo antitumor efficacy is still little known. 34,44 Our previous results on ruthenium(II) and iridium(III) organometallic complexes of the types [Ru(C^N)(N^N) 2 ] + , [Ir-(C^N) 2 (N^N)] + , and [Ir(C^N)(N^N^N)] + demonstrated that slight modifications on the benzimidazole-based ligand core rendered high anticancer activities in vitro, 45−49 the Nsubstituted butyl group serving to adjust the lipophilic properties and enhance cellular uptake and targeting preferentially mitochondria, 45,46 whereas the ester group attached to the benzimidazole backbone could act as a handle for further functionalization. 50 Herein, we report a new series of nine rhenium(I) complexes of the type fac-[Re(CO) 3 the thought that the electron-deficient nature of the benzothiazole moiety could led to a red-shift of the emission maximum of the Re complexes compared to that of those containing the 2-pyridyl-benzimidazole ligand L1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…33,36−43 However, their in vivo antitumor efficacy is still little known. 34,44 Our previous results on ruthenium(II) and iridium(III) organometallic complexes of the types [Ru(C^N)(N^N) 2 ] + , [Ir-(C^N) 2 (N^N)] + , and [Ir(C^N)(N^N^N)] + demonstrated that slight modifications on the benzimidazole-based ligand core rendered high anticancer activities in vitro, 45−49 the Nsubstituted butyl group serving to adjust the lipophilic properties and enhance cellular uptake and targeting preferentially mitochondria, 45,46 whereas the ester group attached to the benzimidazole backbone could act as a handle for further functionalization. 50 Herein, we report a new series of nine rhenium(I) complexes of the type fac-[Re(CO) 3 the thought that the electron-deficient nature of the benzothiazole moiety could led to a red-shift of the emission maximum of the Re complexes compared to that of those containing the 2-pyridyl-benzimidazole ligand L1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, the mechanisms of action of Re(I) anticancer complexes containing the fac -[Re(CO) 3 ] + core are quite distinct from that of conventional platinum agents, , that is dependent on covalent bond formation to DNA . Targeting vulnerable organelles, such as the mitochondria, is one strategy that has been employed to combat resistance to chemotherapeutics, and that generally is the case for rhenium(I) tricarbonyl complexes. , However, their in vivo antitumor efficacy is still little known. , Our previous results on ruthenium(II) and iridium(III) organometallic complexes of the types [Ru(C^N)(N^N) 2 ] + , [Ir(C^N) 2 (N^N)] + , and [Ir(C^N)(N^N^N)] + demonstrated that slight modifications on the benzimidazole-based ligand core rendered high anticancer activities in vitro , the N-substituted butyl group serving to adjust the lipophilic properties and enhance cellular uptake and targeting preferentially mitochondria, , whereas the ester group attached to the benzimidazole backbone could act as a handle for further functionalization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation